Y = x^2- 7x - 8 = 0x^2/3 - 7x/3 = 8/3.
Multiply both sides by 3:
x^2 - 7x - 8 0
C = -8 = 1*(-8) = 2*(-4).
Choose the pair of factors whose sum=-7
Y = (x-8)(x+1) = 0.
what are the step in changing this equation to factored form?
y= 1/3 x^2 - 7/3x = 8/3
2 answers
Correction:
Y = x^2/3- 7x/3 = 8/3
Multiply both sides by 3:
x^2 - 7x = 8
x^2 - 7x - 8 = 0
C = 8 = 1*(-8) = 2*(-4).
Choose the pair of factors whose sum=-7.
Y = (X-8)(X+1) = 0.
Y = x^2/3- 7x/3 = 8/3
Multiply both sides by 3:
x^2 - 7x = 8
x^2 - 7x - 8 = 0
C = 8 = 1*(-8) = 2*(-4).
Choose the pair of factors whose sum=-7.
Y = (X-8)(X+1) = 0.